Christian Ethics and Distance Education (Conference Series, 2022)
Ever since the declaration of the Covid-19 pandemic as a worldwide crisis, the educational approach across the world has undergone a transformation. Both teachers and students are using an online method of teaching and learning. In applying this method, they experience a new challenge related to the moral and ethical aspects of online learning or distance education. This study aims to determine the application of Christian ethics in distance education. It uses a qualitative approach. The study suggests that incorporating Christian ethics, which are founded on the principles of God’s teachings, should be integrated into distance education, as secular ethical principles are insufficient in establishing the value of absolute truth. Utilizing Christian ethical principles as a compass can serve as a reliable method for addressing moral and ethical inquiries. It has the potential to positively impact individuals who follow it. By embracing it as a solution, one can reduce or even conquer any challenges associated with ethical dilemmas.